0210 „Mitglied (kein Amt, kein Rang)“ - Bettina Keß (RIHA Journal, 2019)
Christian Schad (1894–1982) is regarded as one of the most important representatives of New Objectivity (Neue Sachlichkeit) in Germany and best known as a painter of the Berlin society during the Weimar Republic. Research, art criticism and exhibitions have long classified him as an artist who neither politically nor artistically adapted to the Nazi regime (1933–1945). Schad himself described his attitude towards National Socialism as critical in retrospect. This essay questions both the self-image of the painter and graphic artist and his reception after 1945 as an artist critical of the regime who deliberately withdrew from the art market. Based on archival material regarding the artist's life and work, this article shows that Christian Schad had actually been a member of the National Socialist German Workers' Party (NSDAP) since 1933, continued to be represented in exhibitions and publications, and also somewhat adjusted his motifs and style to the favoured taste in art.